(3efMfi fXejs - (3YHO GdHGQj GHQGgje(B, (3OQIs; (3RgjQ fYje GdUHGZ(B, s ((3YeGf(B:s (3OGQ hGFd(B,s, 2008)
(3GOGQI GdehGQO GdHTQjI JMOjO Gdeaghe, GOGQI GdehGQO GdHTQjI GdNdajI GdJGQjNjI hGdYhGed hGdMQcGJ GdJj JDKQ YdjgG aj GdYGde aj eWdY GdbQf GdMGOj hGdYTQjf, GOGQI GdehGQO GdHTQjI cfXGe, hVY GSJQGJjLjI ddehGQO GdHTQjI, JMdjd GdhXGFa, JNWjW GdehGQO GdHTQjI, Jbjje GdCOGA, GdJOQjH hGdJfejI, JMOjO GdQhGJH hGdCLhQ, age OGaYjI GdYGedjf hMaRge heYGdLI ChVGYge heTcdGJge, eSJbHd GOGQI GdehGQO GdHTQjIs
(3HHdjhZQGajG(B: (3U(B.497s
Keywords: (3GOGQI GdGYeGds; (3GOGQI GdGaQGOs; (3Gdbhi GdYGedIs